Corporate Culture and Employee Performance: The Role of Vision, Mission, Norms, and Employee Focus - Az-Zaakiyyah, Hizbul Khootimah; Ausat, Abu Muna Almaududi; Suherlan, Suherlan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
In the era of globalization and increasingly fierce business competition, a profound understanding of how corporate culture influences employee performance has become a primary focus for organizational leaders and managers. The purpose of this research is to analyze the influence of corporate culture on employee performance. This study is a qualitative descriptive study that explores previous studies related to corporate culture and employee performance. First, relevant studies were collected regarding corporate culture and employee performance, as well as the possible impacts of these constructs. Subsequently, the author summarized the relevant studies and discussed the concepts of corporate culture and employee performance and how these concepts can be utilized within organizations. The next step is to express the author's views on the potential of corporate culture and employee performance within the organization. The study results indicate that corporate culture, including clear vision and mission, emphasized norms, and employee-focused orientation, significantly influences employee performance. A strong and positive culture shapes an inspirational work environment, motivates employees to contribute their best, enhances productivity, work quality, and teamwork, and provides a competitive advantage for the company in achieving its goals and success. Corporate culture also plays a crucial role in employee retention, attracting top talents, and differentiating the company in the job market.